Women's Participation in the Tubectomy Family Planning Program in Batuda Pantai District, Gorontalo Regency - Umriany T. Laudengi; Thalib , Tety; Kadir, Jusrin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine women's participation in the Tubectomy Family Planning Program in Batudaa Pantai District, Gorontalo Regency. With research sub-focus, namely family support, knowledge and attitudes. This research uses a qualitative descriptive research type. The data collection techniques used are: Observation techniques, interviews and secondary data recording. In accordance with the type of research used, the data analysis technique used is qualitative analysis technique. The research results show that from the aspect of family support it is still lacking, from the aspect of knowledge and attitude it does not support the Tubectomy family planning program. Overall, research regarding women's participation in the Tubectomy Family Planning Program which is seen from the aspects of family support, knowledge and attitudes does not support the Tubectomy Family Planning program. The things suggested in this research are the need for local governments, especially the BKKBN, to pay attention to aspects that become obstacles in implementing the Tubectomy Family Planning program, such as aspects of family support, knowledge and attitudes. Because it does not rule out the possibility that these aspects will support the Tubectomy Family Planning Program in the future.